Resonant interaction between fusion products and magnetic field perturbations in toroidal magnetic trap with the rotational transform - Moskvitina, Yu.K.; Shishkin, A.A. (Вопросы атомной науки и техники, 2008)
The resonance condition for “particle – magnetic field perturbation” interaction is obtained under the solving of the drift kinetic equation. The resonance phenomenon in the particle motion in dependence on the radial position in the vertical cross-section of torus is studied. Both numerical and the analytical treatment for the cold α-particles motion near resonant condition in toroidal magnetic trap are presented. При розв’язку дрейфового кінетичного рівняння отримана резонансна умова для взаємодії «частинка – збурювальне магнітне поле». Досліджені резонансні явища у русі частинки в залежності від радіального положення в вертикальному перерізі тору. Чисельним інтегруванням рівнянь руху отримано траєкторії резонансних «холодних» α-частинок і представлено аналітичне трактування отриманих результатів. При решении дрейфового кинетического уравнения получено резонансное условие для взаимодействия «частица – возмущающее магнитное поле». Изучены резонансные явления в движении частицы в зависимости от радиального положения в вертикальном сечении тора. Численным интегрированием уравнений движения получены траектории резонансных «холодных» α-частиц и дана аналитическая трактовка полученных результатов.